1999
DOI: 10.1111/j.1151-2916.1999.tb02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear of Alumina/Silicon Carbide Nanocomposites

Abstract: The wear resistance of four Al 2 O 3 /SiC nanocomposites that contained SiC particles of varying average size (40, 200, and 800 nm) was studied under dry sliding conditions and compared with the results obtained in unreinforced alumina. The wear rate of the alumina and the nanocomposites of equivalent grain size increased as the contact load increased; however, the nanocomposite wear resistance at high contact loads was better than that of the alumina by a factor of 3-5. The wear resistance of the nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 14 publications
6
42
0
Order By: Relevance
“…The fracture toughness is slightly higher than the toughness of monolithic aluminas (typically 3-4 MPa m 1/2 ) and is comparable to the values usually reported for Al 2 O 3 -SiC micro-nanocomposites. However, our recent results indicate that the resistance of polymer-derived alumina-SiC nanocomposites to abrasive wear has, in accord with previously published data, [23][24][25] markedly improved with respect to monolithic polycrystalline alumina with comparable grains size. A detailed summary of the results is in preparation.…”
Section: Resultssupporting
confidence: 88%
“…The fracture toughness is slightly higher than the toughness of monolithic aluminas (typically 3-4 MPa m 1/2 ) and is comparable to the values usually reported for Al 2 O 3 -SiC micro-nanocomposites. However, our recent results indicate that the resistance of polymer-derived alumina-SiC nanocomposites to abrasive wear has, in accord with previously published data, [23][24][25] markedly improved with respect to monolithic polycrystalline alumina with comparable grains size. A detailed summary of the results is in preparation.…”
Section: Resultssupporting
confidence: 88%
“…The smaller sizes led to the more wear resistant composites due to a change in the fracture mode from brittle intergranular fracture to plastic deformation. Rodriguez et al 13 carried out reciprocating ball-on-flat wear tests on Al 2 O 3 and different Al 2 O 3 /SiC composites containing either submicron particles (800 nm) or nanoparticles (40 and 200 nm) of SiC. At high contact loads, the nanocomposites increased their wear resistance in two orders of magnitude referred to the base Al 2 O 3 , meanwhile the submicron SiC particles only increased its wear resistance by a factor of ∼5.…”
Section: Introductionmentioning
confidence: 96%
“…It was observed that the fracture changed from intergranular in the composites containing coarse SiC particles to transgranular in the nanocomposites. 4,5 The tribological properties of Al 2 O 3 composites containing SiC whiskers, platelets or nanoparticles have been also studied, [6][7][8][9][10][11][12][13][14][15] although a comprehensive analysis of data reported in the literature is complicated, due to the wide gamut of test configurations and experimental parameters. As a general rule, the addition of SiC particles improves the wear resistance of the composites compared to that of the monolithic alumina as detailed below.…”
Section: Introductionmentioning
confidence: 99%
“…The residual stresses drive near-surface cracks that can lead to material removal in these processes. A recent example of such an investigation is provided by the work of Wu et al [5], who studied indentations and scratches in Al 2 O 3 and Al 2 O 3 /SiC nanocomposites in order to further the understanding of the improved surface finish and wear resistance of the nanocomposites compared with Al 2 O 3 [6][7][8][9][10][11]. The investigation centred on residual stress measurements by Cr 3+ fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%